2016
DOI: 10.1080/15384047.2016.1210736
|View full text |Cite
|
Sign up to set email alerts
|

Methylglyoxal suppresses human colon cancer cell lines and tumor growth in a mouse model by impairing glycolytic metabolism of cancer cells associated with down-regulation of c-Myc expression

Abstract: Methylglyoxal (MG) is a highly reactive dicarbonyl compound exhibiting anti-tumor activity. The antitumor effects of MG have been demonstrated in some types of cancer, but its role in colon cancer and the mechanisms underlying this activity remain largely unknown. We investigated its role in human colon cancer and the underlying mechanism using human colon cancer cells and animal model. Viability, proliferation, and apoptosis were quantified in DLD-1 and SW480 colon cancer cells by using the Cell Counting Kit-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…Cell apoptosis was detected using the Annexin V-APC Apoptosis Detection kit (KeyGEN Biotech, Nanjing, China) as described in our previous studies and others [41,42,43,44]. Allophycocyanin (APC) is an accessory photosynthetic pigment found in blue-green algae.…”
Section: Methodsmentioning
confidence: 99%
“…Cell apoptosis was detected using the Annexin V-APC Apoptosis Detection kit (KeyGEN Biotech, Nanjing, China) as described in our previous studies and others [41,42,43,44]. Allophycocyanin (APC) is an accessory photosynthetic pigment found in blue-green algae.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies demonstrated that ATB acts as a competing RNA by binding with microRNA (miR)-494 in lung cancer cells (28), miR-141-3p in gastric cancer cells (29), miR-590-5p in melanoma (30), and miR-200 family members in diverse types of cancer (18,26,31,32). ATB regulates transcriptional coactivator YAP1 (YAP1), NF-ÎşB, p38 mitogen-activated protein kinase (MAPK), Twist, and TGF-β in lung cancer, glioma, breast cancer and malignant melanoma (23,30,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were seeded into the upper chambers of the transwell culture plates (SW480, 8Ă—10 4 cells; SW620, 1.2Ă—10 5 cells; DLD-1, 8Ă—10 4 cells; and HCT-15, 8Ă—10 4 cells), and RPMI-1640 medium containing 20% FBS was placed in the lower chambers as a chemoattractant. The cells were seeded into the upper chambers of the transwell culture plates as described in our previous paper [ 13 ]. The invasion assay was similar to the migration assay except that the inserts were coated with 45 uL matrigel solution (matrigel: serum-free medium ratio 1:10).…”
Section: Methodsmentioning
confidence: 99%
“…Methylglyoxal (MG), an extremely reactive glucose metabolite, is an endogenous byproduct of glycolysis. It is mainly generated in the dephosphorylation of glycolytic intermediates and in metabolism of the polyol pathway and amino acetone [ 8 – 13 ]. MG was historically investigated as an antitumor agent, but sound scientific evidence of its efficacy is lacking [ 9 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation